Evaluación del cultivo de ají tabasco (capsicum frutescens) con fertilizante inorgánico en la parroquia Guasaganda del cantón La Maná. - Cedeño Masapanta, Danny Adrian (2023)
This project was carried out in the Los Pachacos Campus, belonging to the Guasaganda Parish of La Maná Canton, with a geographical location WGS latitude 0°48'00.0"S longitude 79°10'01.2"W, with an altitude of 200 at 3,200 masl, the project lasted 120 days. The objective was to evaluate the cultivation of tabasco pepper (Capsicum frutescens) by applying different doses of inorganic fertilizer in the Guasaganda Parish of La Maná Canton. For the statistical analysis of the present investigation, the statistical software INFOSTAT 2022 was used in which the Tukey test was applied to the %% of statistical probability, the variables evaluated were: plant height (cm), stem diameter (cm), days until flowering, number of fruits per plant (unit), fruit length (cm), fruit diameter (cm), fruit weight (g) and yield (kg). In conclusion, the investigation showed that applying the physical mixture in the tabasco pepper crop has positive effects on the production of the crop, being the best the T3 physical mixture (15-15-15) 125 g, winning in most of the variables evaluated. The production cost analysis of the different treatments managed in the project determined that the treatment with the best net benefit is a physical mixture (15-15-15 NPK) 125 g, obtaining a value of 13.95 dollars.